Undergraduates' perspective on a pedagogical architecture to requirements engineering education - Santana, Thalia S.; Kudo, Taciana N.; Bulcao-Neto, Renato F. (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2023: Anais do XXXVII Simpósio Brasileiro de Engenharia de Software, 2023)
The literature has revealed the misalignment between higher education and professional practice in Requirements Engineering (RE). An alternative approach to mitigate this problem is adopting a pedagogical architecture (PA), which structures and diversifies the pedagogical practice of RE theory. This paper presents the evaluation of a PA to the education on requirements specification and validation. Undergraduate students of three RE classes at a Brazilian public university experimented and evaluated, through a survey, the PA’s lesson plans, teaching materials, and practical activities. From the analysis of 153 responses, we have shown that a PA to RE education can contribute to aligning RE knowledge and essential hard and soft skills for graduating future requirements analysts.